AN ANALYSIS OF JARGONS USED BY THE MEDICAL STAFF IN RSUP DR. SARDJITO YOGYAKARTA - Idha Nurbaiti; Yose Rianugraha (Conscientia, 2021)
This research aims at analyzing the word formation process of the jargon and revealing the meaning of the jargons used by the medical staff in RSUP Dr. Sardjito Yogyakarta. This research used a descriptive qualitative method. The data of the research were the jargons used by the medical staff in RSUP Dr. Sardjito Yogyakarta, especially from the Cardiology, Neurology, Surgical, Ophthalmology, and Pediatrics. Descriptive qualitative method was used for this research. The subjects of this research were five people working as medical staff in RSUP Dr. Sardjito Yogyakarta. The research instruments of this research were observation and interview. The findings of this research reveal that there are 69 jargons with four of word formation processes; word borrowing (2 items or 3%), compounding (12 items or 18%), word derivation (53 items or 76%), and acronyms (2 items or 3%). The form of jargons used in medical fields is mostly a code that refers to diagnose in the medical record. It is important for medical staff to master the medical jargons to avoid mistakes in the diagnoses.